Optical analysis of RE3+ (RE = Pr3+, Er3+ and Nd3+):cadmium lead boro tellurite glasses. (27th January 2016) - Giridhar, P.; Bhushana Reddy, M.; Neelima, G.; Ramanaiah, R.; Nagamuni Reddy, K.; Sahadeva Reddy, V.; Sudhakar Reddy, B.
Abstract: This article reports on the optical characterization of Pr 3 + ‐, Er 3 + ‐ and Nd 3 + ‐doped cadmium lead boro tellurite (CLBT) glasses prepared using the melt quenching method. The visible–near infrared (Vis–NIR) absorption spectra of these glasses were analyzed systematically. On measuring the NIR emission spectra of Er 3 + :CLBT glasses, a broad emission band centered at 1536 nm ( 4 I13 /2  →  4 I15 /2 ) was observed, as were three NIR emission bands at 900 nm ( 4 F3 /2  →  4 I9 /2 ), 1069 nm ( 4 F3 /2  →  4 I11 /2 ) and 1338 nm ( 4 F3 /2  →  4 I13 /2 ) from Nd 3 + :CLBT glasses and an NIR emission band at 1334 nm ( 1 G4  →  3 H5 ) from Pr 3 + :CLBT glasses at an excitation wavelength ( λ ex ) of 514.5 nm (Ar + laser). Copyright © 2016 John Wiley & Sons, Ltd.